Blue-Collar Workers Entrepreneurial Intentions and The Extended Theory of Reasoned Action: Incorporating SEM and Person-Item Map Analysis - Hermansyah Andi Wibowo; Nurul Indarti (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: Blue-collar workers face major threats related to the development and application of Industry 4.0. Unfortunately, research on how they deal with this situation is scarce in the behavioral science literature. In this study, we attempt to fill this gap by emphasizing a methodological aspect of combining structural equation modeling (SEM) and person-item map analysis to the extended model of the theory of reasoned action. Novelty and Methods: We offer the notion of combining SEM and Rasch model analysis to explain the extended of theory of reasoned action. The respondents were blue-collar workers from Indonesia who have not yet started a business. Finding/Results: In line with our goal of applying intersubjective certification to the extended theory of reasoned action (TRA) model in the context of blue-collar workers, our results suggest that religiosity affects entrepreneurial intentions, both directly and indirectly, through attitude. The subjective norms have also been shown to influence the intention of blue-collar workers to become entrepreneurs. The extended TRA model has been proven empirically to have good predictive power, with a total effect of 83%. Conclusion: Regarding the sample issue, the person-item map is excellent for explaining our SEM-based findings. The idea of combining the Rasch model property, which is a persons-items map, requires more empirical support to promote its ability to illuminate SEM-based research explanations.